Do not forget Burkitt´s lymphoma! unusual case of primary malignant lymphoma of the prostate in a young patient (2019)
Primary Burkitt´s lymphoma (BL) of the prostate is rare in the adolescent population. The etiology remains poorly understood. There has been some proposed associations to Epstein-Barr virus and HIV. Clinical and histopathologic data of a 17-year-old patient who underwent transurethral resection of the prostate was obtained. We report the first case of primary malignant BL of the prostate in a 17-year-old Caucasian male who presented with hematuria, lower urinary tract symptoms. Differential diagnosis of a prostatic mass in adolescent patients must be primary or secondary lymphoma of the prostate, including BL as described for the first time in this article.